Comparison of Pressure Losses Calculations by Approximate Methods in the Annulus (Laminar Flow) - Almahdawi, Faleh (Iraqi Journal of Science, 2023)
Most of the world’s drilling companies use API method for calculating thepressure drop in drilling oil and gas wells. Iraqi Drilling Company also uses thismethod for drilling oil wells in all fields of Iraq. In Russia, the method is activelyused Grodde for calculating the pressure drop in drilling oil and gas wells. Thisstudy includes a comparison of formulas API, Grodde and new techniquesdeveloped methods for the laminar flow of viscoplastic fluids in the annular space.The aim of this study is to determine the most accurate way to calculate the pressureloss in drilling oil wells. The comparison was focused on identifying changes in thevalues of β, using the above calculation methods.